How to Promote Social Entrepreneurship on Urban Education? An Active Learning Implementation - Capella-Peris, Carlos; Cosgrove, Mary Margaret; Salvador-García, Celina; Maravé-Vivas, María (Education and urban society, 2022)
This paper analyzes the effects of active learning (AL) on the social entrepreneurship (SE) of physical education teacher education students (n = 158) from an Urban School. AL participants applied several strategies including but not limited to flipped classroom, problem solving, team projects, or case studies. The topic was approached using mixed methods with methodological triangulation. Quantitative evidence was gathered through a quasi-experimental design of six non-equivalent groups implementing the Social Entrepreneurship Competency Scale (SECS). Meanwhile, qualitative analysis was undertaken analyzing 119 reflective journals. Quantitative results provide significant evidence regarding the positive effect of AL on SE. Qualitative analysis complements this view describing how SE was developed (e.g., providing-receiving feedback among peers). Additionally, data transformation displays an alternative analysis of the benefit provided. Our results display how AL improves SE of physical education teacher education students, enhancing new research into this direction to meet current education demands.
Keywords: active learning; social entrepreneurship; physical education teacher education; mixed methods; higher education; JCR; Scopus